Towards a natural classification of Dothideomycetes 4: The genera Bryopelta, Bryorella, Bryosphaeria, Lophiosphaerella and Maireella (Dothideomycetes incertae sedis) - Wen-Jing, Li; Bhat, Jayarama D.; Hyde, Kevin D.; Wang, Yong (Phytotaxa, 2014)
In the latest classification of Ascomycota with 365 genera in the Dothideomycetes, most taxa are poorly known. In this paper we re-examine the type species of Bryopelta, Bryorella, Bryosphaeria, Lophiosphaerella and Maireella. By studying the generic types we suggest higher level placement and better understanding of morphology of these genera. It is hoped that this will stimulate fresh collections and sequence data for these genera so that we can place the taxa in a natural classification system.